Plants arrangement and number of seeds per hole in the agroeconomic yield of pea - Torales, Elissandra Pacito; Zárate, Néstor Antonio Heredia; Vieira, Maria do Carmo; Gutierrez, Robson Santos; Gassi, Rosimeire Pereira; Tabaldi, Luciane Almeri (Semina: Ciências Agrárias, 2014)
The aim of this work was to study the 'luciana 50' pea, cultivated with different numbers of rows of plants in the plot and with two and three seeds per hill. The work carried out in Dourados-MS, between March-July 2010. Treatments were arranged in 3 x 2 factorial in randomized complete block design with six replicates. Populations corresponding to the sowing with two, three and four rows per plot were 264,000, 396,000 and 528,000 plants ha-1, respectively, with two seeds per hill, and 396,000, 594,000 and 792,000 plants ha-1, respectively, with three seeds per hill. The harvest was done at 108 days after sowing. In cultivation with four rows of plants and two seeds per hill, were obtained the highest yields of fresh and dry weight of grains and pods commercial, with increases of 29.88%, 33.85%, 29.14% and 32.22%, respectively, and higher number of grains and pods commercial, with increases of 28.13% and 27.12%, respectively, over two rows of plants with two seeds per hill. The highest yield of fresh weight of shoots, of bark and of non-commercial pods were with four rows of plants, with increases of 1.75 t ha-1, 0.44 t ha-1 and 0.47 t ha-1 respectively, compared to two rows. Considering the yield of commercial pods and grains and the estimated net income, it can be concluded that sowing of 'Luciana 50' pea should be performed with four rows of plants and two seeds per hill.